2015
DOI: 10.5152/ced.2015.1662
|View full text |Cite
|
Sign up to set email alerts
|

Candida Pelliculosa Fungemia Cases in Pediatric Intensive Care Unit

Abstract: Candida pelliculosa (teleomorph: Wickerhamomyces anomalus) is an opportunistic pathogen that rarely causes fungemia. Here we present two cases with C. pelliculosa fungemia in the pediatric intensive care unit. The fungemia developed as a result of horizontal transmission from a patient who was transferred from another hospital with the same condition. Strains isolated from blood cultures of the two patients were identified as Candida pelliculosa with API ID 32C (bioMerieux France) commercial kit. All strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Despite being uncommon, the role of this pathogen causing outbreaks has been reported in children. 4,15,29,30 Similarly, C. glabrata in another study has reported increase from 2.6% in 2003 to 23.7% in 2012. 12 There were significant differences in Candida spp.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite being uncommon, the role of this pathogen causing outbreaks has been reported in children. 4,15,29,30 Similarly, C. glabrata in another study has reported increase from 2.6% in 2003 to 23.7% in 2012. 12 There were significant differences in Candida spp.…”
Section: Discussionmentioning
confidence: 86%
“…has been a global concern in recent times. 6,9,10,14,15 There has been an increase in the proportion of infections due to C. glabrata and C. parapsilosis in the last few decades. These species show higher levels of resistance to antifungal agents and therefore might be associated with higher mortality than C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 243 articles from PubMed and Scopus were screened. Finally, 36 met the present study’s inclusion criteria [ 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These 36 studies involved 170 patients in total.…”
Section: Resultsmentioning
confidence: 99%